Recovery of valuable metals from pyrite produced in copper flotation by a roasting-leach method - Ozer, A.; Tumen, F.; Bildik, M. (My University, 1993)
Pyrite concentrate, produced as by-product during the flotation of pyritic copper ore, contains significant amount of cobalt. In this study, recovery of cobalt, copper and nickel by a roasting-leach method from the pyritic concentrate of Etibank Ergani copper Plant was investigated. For this purpose, the effect of roasting and leaching parameters on the metal extraction was studied. Starting with 10g pyrite and providing the optimum conditions were experimentally established, such as roasting at 500 degreesC for 120 minutes 20% pulp density, adding 70mg CaCO "SUB 3" to calcine and leaching at ambient temperature for 30 minutes, the recovery of Co, Cu, and Ni were 70.2%, 61.0%, and 14.4% respectively. 0.65% of the iron present in the pyrite was found to be passed in to the solution under the above conditions. Thus the valuable metals present in the pyritic concentrate could be recovered if a roasting system with temperature control was utilized. (English summary)
Bakir flotasyon artigi piritten kavurma-lic yontemiyle degerli metallerin kazanilmasi
Keywords: Copper; Flotation; Metal; Recovery